Pemanfaatan Mikrotik RB942-2ND Menggunakan Metode Firewall Filtering Untuk Keamanan Jaringan Dengan Model Forensik - Sulaiman, Rahmat; Mardeka Raya, Agustina; Laurentinus, Laurentinus; Padli, Padli (Jurnal Teknologi, Fakultas Teknik, Universitas AKPRIND Indonesia, 2024)
Nowadays as demand for fast and effective services increases, global technological and telecommunications developments also increase. Every village office, one of which is Belo Laut, must have an internet network to serve the community in accessing community data, therefore the development of technology and telecommunications is also very important for the government. To create a safe and effective internet network, this network security system uses Mikrotik with the Firewall Filtering method. The research problem is how to design and build network security in the Belo Laut village office area using Mikrotik to prevent the negative impacts of the internet, such as sites with adult content. Layer 7 protocol configuration and Filter Rules are included in blocking. Based on the keywords that have been determined, the test results show that Mikrotik has succeeded in blocking sites or websites that contain adult content.